Emily Bronte’s Use of Symbolic Seasonal Imagery in Poetry - Dr. Khalefa Alsadek Albakoush (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
Poetry is renowned for its sophisticated and nuanced language which is often meant to evoke emotions and convey messages implicitly. To achieve this, poets frequently employ various techniques, styles and symbols. Some of the symbols may create ambiguity for inexperienced readers. For instance, a highly reoccurring theme in poetry is the use of seasonal imagery. Emily Bronte deploys it extensively in her works. This paper examines Bronte’s use of seasonal symbolism, providing definitions and examples of various forms of symbolism. The analysis focuses on selected poems by Bronte, scrutinizing the types, meanings, and reasons for the use of symbols. The findings show that Bronte employs seasonal imagery to create vivid and aesthetically engaging images in her work. The paper concludes by recommending further exploration of symbolism in poetry as a means to deepen appreciation for the genre and its intricacies.